Study of Tuberculosis in Rhesus macaques of Nepal - Shrestha, S.P.; Shrestha, D.; Prajapati, M.; Shrestha, S.P. (Nepalese Veterinary Journal, 2017)
Tuberculosis is one of the prioritized zoonotic diseases in Nepal producing severe health hazard in humans and animals including both wildlife species and livestock species. It is also one of the most important bacterial diseases of nonhuman primates, especially macaques which is caused by Mycobacterium tuberculosis and M. bovis. A study was conducted from 2010 to 2012 in macaques of Nepal to find out the status of tuberculosis. Altogether 326 macaques were tested for tuberculosis by Intradermal Skin test on the eyelid and M. tuberculosis/M. bovis antibody testkit. Out of 326 macaques tested, 62 were found positive for the tuberculosis. So, the overall prevalence rate of tuberculosis in rhesus macaques was found to be 19.02%. From the study it is concluded that not only humans, but the monkeys are also equally vulnerable to this disease condition and produce more severe health hazards, resulting even in death. These macaques should also be given priority concerning this as they may pose risk to other wild life species and humans. More researches should be directed towards exploring disease condition and status in these animals to protect other wildlife species and human contacting this disease.